Are physicians prepared for whole genome sequencing? a qualitative analysis. Issue 2 (7th July 2015) - Christensen, K.D.; Vassy, J.L.; Jamal, L.; Lehmann, L.S.; Slashinski, M.J.; Perry, D.L.; Robinson, J.O.; Blumenthal‐Barby, J.; Feuerman, L.Z.; Murray, M.F.; Green, R.C.; McGuire, A.L.; et al.
Abstract : Although the integration of whole genome sequencing (WGS) into standard medical practice is rapidly becoming feasible, physicians may be unprepared to use it. Primary care physicians (PCPs) and cardiologists enrolled in a randomized clinical trial of WGS received genomics education before completing semi‐structured interviews. Themes about preparedness were identified in transcripts through team‐based consensus‐coding. Data from 11 PCPs and 9 cardiologists suggested that physicians enrolled in the trial primarily to prepare themselves for widespread use of WGS in the future. PCPs were concerned about their general genomic knowledge, while cardiologists were concerned about how to interpret specific types of results and secondary findings. Both cohorts anticipated preparing extensively before disclosing results to patients by using educational resources with which they were already familiar, and both cohorts anticipated making referrals to genetics specialists as needed. A lack of laboratory guidance, time pressures, and a lack of standards contributed to feeling unprepared. Physicians had specialty‐specific concerns about their preparedness to use WGS. Findings identify specific policy changes that could help physicians feel more prepared, and highlight how providers of all types will need to become familiar with interpreting WGS results. Abstract : Section Editor: Aad Tibben, email:a.tibben@lumc.nl